Cryopreserved PM21-Particle-Expanded Natural Killer Cells Maintain Cytotoxicity and Effector Functions In Vitro and In Vivo - Oyer, Jeremiah L.; Croom-Perez, Tayler J.; Dieffenthaller, Thomas A.; Robles-Carillo, Liza D.; Gitto, Sarah B.; Altomare, Deborah A.; Copik, Alicja J. (Frontiers in Immunology, 2022)
There is a great interest in developing Natural Killer (NK) cells as adoptive cancer immunotherapy. For off-the-shelf approaches and to conduct multi-center clinical trials, cryopreserved NK cells are the preferred product. However, recent studies reported that cryopreservation of NK cells results in loss of cell motility and, as a consequence, cytotoxicity which limits the clinical utility of such products. This study assessed the impact of cryopreservation on recovery and function of PM21-particle expanded NK cells (PM21-NK cells) as well as their anti-tumor activity in vitro using 2D and 3D cancer models and in vivo in ovarian cancer models, including patient-derived xenografts (PDX). Viable PM21-NK cells were consistently recovered from cryopreservation and overnight rest with a mean recovery of 73 ± 22% (N=19). Thawed and rested NK cells maintained expression of activating receptors when compared to expansion-matched fresh NK cells. Cryopreserved NK cells that were thawed and rested showed no decrease in cytotoxicity when co-incubated with tumor cells at varying effector-to-target (NK:T) ratios compared to expansion-matched fresh NK cells. Moreover, no differences in cytotoxicity were observed between expansion-matched cryopreserved and fresh NK cells in 3D models of tumor killing. These were analyzed by kinetic, live-cell imaging assays co-incubating NK cells with tumor spheroids. When exposed to tumor cells, or upon cytokine stimulation, cryopreserved NK cells that were thawed and rested showed no significant differences in expression of degranulation marker CD107a or secretion of TNFα and IFNγ. In vivo anti-tumor activity was also assessed by measuring extension of survival of SKOV-3-bearing NSG mice treated with fresh vs. cryopreserved NK cells. Cryopreserved NK cells caused a statistically significant survival extension of SKOV-3 bearing-NSG mice that was comparable to that observed with fresh NK cells. Additionally, treatment of NSG mice bearing PDX tumor with cryopreserved PM21-NK cells resulted in nearly doubling of survival compared to untreated mice. These data suggest that PM21-NK cells can be cryopreserved and recovered efficiently without appreciable loss of viability or activity while retaining effector function both in vitro and in vivo. These findings support the use of cryopreserved PM21-NK cells as a cancer immunotherapy treatment.